The National Security Implications of Cyberbiosecurity - George, Asha M. (Frontiers in Bioengineering and Biotechnology, 2019)
The cyber- and biological sciences are converging rapidly, increasing risk to the nation and our bioeconomy. The parts of the U.S. public and private sectors that should be responsible for cyberbiosecurity are not yet sufficiently organized or resourced. This article addresses the need to ensure that U.S. national security policy: (1) assesses cyberbiological risk and incorporate deterrent and enforcement measures; (2) sets forth clear consequences for those individuals and countries that conduct cyberbiological attacks or otherwise compromise national cyberbiosecurity, without imperiling the legitimate sharing of scientific data and information; (3) establishes voluntary standards in partnership with the private sector; (4) identifies cyberbiosecurity threats, vulnerabilities, and consequences created by malware introduced via DNA, pathogen and biomanufacturing data system weaknesses, dual-use synthetic biology, and biological intellectual property theft; and (5) results from the combined efforts of the Executive and Legislative Branches.